DESIGNING A BUSINESS INTELLIGENCE DASHBOARD FOR DEMAND-DRIVEN INVENTORY MANAGEMENT: A CASE STUDY OF MEDIKLUG PHARMACEUTICAL DISTRIBUTION COMPANY - Nicolaus Ernest Mamonto; Leo Aldianto (RADJA PUBLIKA, 2026)
In pharmaceutical distribution, balancing high product variety with fluctuating demand is a constant challenge. When inventory decisions don’t reflect actual customer usage, companies face a frustrating cycle of stock-outs for popular items and dusty shelves for slow-movers—eventually hurting the bottom line. Mediklug, a healthcare tech firm, faced this exact issue; despite having detailed clinic-level consumption data from their EMR system, they saw a significant revenue dip in late 2025. This study explores how to bridge that gap using Demand-Driven Supply Chain (DDSC) principles. By leveraging Business Intelligence (BI), we aimed to turn Mediklug’s